An established protocol for generating transgenic wheat for wheat functional genomics via particle bombardment - Wang, Yaqiong; Zeng, Jian; Su, Peipei; Zhao, Hongyan; Li, Li; Xie, Xiaoxue; Zhang, Qian; Wu, Ya’nan; Wang, Ruibin; Zhang, Yufan; Yu, Boju; Chen, Mingjie; et al. (Frontiers in Plant Science, 2022)
Wheat is one of the most important food crops in the world and considered as one of the top targets in crop biotechnology. With the high-quality reference genomes of wheat and its relative species and the recent burst of genomic resources in Triticeae, demands to perform gene functional studies in wheat and genetic improvement have been rapidly increasing, requiring that production of transgenic wheat should become a routine technique. While established for more than twenty years, the particle bombardment-mediated wheat transformation has not become routine yet, with only a handful of labs being proficient in this technique. This could be due to, at least partly, the low transformation efficiency and the technical difficulties. Here, we describe the current version of this method through adaptation and optimization. We report the detailed protocol of producing transgenic wheat by the particle gun, including several critical steps, from the selection of appropriate explants (i.e., immature scutella), the preparation of DNA-coated gold particles and the several established strategies of tissue culture. More importantly, with over twenty-years experience of wheat transformation in our lab, we share the many technical details and recommendations, and emphasize that the particle bombardment-mediated approach has less limitations in genotype dependency and vector construction when compared with the Agrobacterium-mediated methods. The particle bombardment-mediated method has been successful for over thirty wheat genotypes, from the tetraploid durum wheat to the hexaploid common wheat, from modern elite varieties to landraces. In conclusion, the particle bombardment-mediated wheat transformation has demonstrated its potential and wide applications, and the full set of protocol, experiences and successful reports in many wheat genotypes described here will further its impacts, making it toward a routine and robust technique in the crop research labs worldwide.